Creating the demand for better crime policy: qualitative frame analysis as a vehicle for social transformation - Matthews, Janeille Zorina (Crime, law and social change, 2024)
When the dominant crime narrative embraced by members of the public runs contrary to evidence or exaggerates the incidence or mischaracterises the nature of crime, and the news media reproduce that narrative, lawmakers and politicians tend to justify punitive crime policy and ‘tough on crime’ rhetoric as the ‘will of the people’ and a necessary measure to restore ‘law and order’. As such, the way in which members of the public and the news media understand crime and what they say about it is important because of the influence such discourse can have on criminal justice policy. But, in this paper I argue that Qualitative Frame Analysis (“QFA”) can be an effective methodological tool in shifting problematic narratives and facilitating social change. Using QFA, researchers, policymakers and advocates can positively shape crime discourse and design evidence-based policy proposals that are not only politically palatable but also criminologically sound. Using the case of Antigua and Barbuda, an Anglophone Caribbean country in the Eastern Caribbean, I argue that QFA can contribute to progressive crime policy in Antigua and Barbuda – policy that is informed by an understanding of crime that does not have at its heart notions of “law and order” or “getting tough.” Additionally, I show the importance of including the experiences of the global south in the extant literature as this case expands the working catalogue of culturally available crime frames beyond those identified in Europe and North America.